Digital Innovation Strategies in Sharia Cooperative Business Transformation: Mobile App Impact on Financial Performance and Member Satisfaction - Bakhri, Saiful; Rofiq, Aunur; Faizum, Dikril (Revenue Journal: Management and Entrepreneurship, 2025)
This study examines digital innovation strategies in the transformation of sharia cooperative businesses, focusing on the impact of mobile app implementation on financial performance and member satisfaction. A case study was conducted on KSPPS BMT UGT Nusantara, a microfinance sharia institution that has adopted digital technology in its services. Using a mixed-methods approach, the research analyzes data from in-depth interviews, member surveys, and institutional financial reports from 2018-2023. Findings reveal that adopting mobile apps significantly increased the cooperative’s fee-based income by an average of 15% annually since implementation. Factors such as ease of use, transaction security, and incentive programs play vital roles in technology adoption among members. However, challenges such as digital gaps across member generations and the need for improved digital literacy were identified. Member satisfaction analysis shows a 20-point increase in Net Promoter Score (NPS), indicating a positive impact of digital innovation on member loyalty. The study also reveals that digital transformation has driven operational efficiency, with a 5% decrease in the operating cost to operating income ratio (OER) over the last two years. This research contributes theoretically and practically to understanding the role of digital innovation in sharia cooperative business transformation. The findings highlight the importance of comprehensive digital strategies focused on technology adoption, member digital capability development, and business model adjustment. Managerial implications include recommendations for sustained technology investment, digital education programs for members, and data-driven service development to enhance the value proposition of sharia cooperatives in the digital era.